(untitled) (Annals of Medical Research, 2022)
Aim: Cardiac implantable electronic devices (CIED) have been increasingly used in recent years; consequently, there has been an increment in device-related complications. In this study, we aimed to make a recommendation to the centers that can implant cardiac devices about perioperative measures and to reinforce the role of perioperative measures in preventing cardiac device infection. Materials and Methods: The retrospective review examined the patients demographic data, medical diagnoses, operation details, echocardiographic findings, anticoagulant/ antiaggregant usement and complications (Table 1), laboratory findings and comorbidities (Table 2). No distinction was made between device types. A 90-day and a 30-day retrospective screening were performed. Patients were scheduled for follow-up visits one week and one month after the procedure. Three-month checks on telecommunication methods were performed. Results: The study included 169 people. There were 60 (35.5%) emergency department patients admitted. A pacemaker was implanted in 60 patients, an implantable cardioverter-defibrillator (ICD) in 79 patients, and a Cardiac Resynchronization Therapy (CRT) in 30 patients. The procedure time of patients with CRT implantation was significantly longer (p <0.001) when battery replacements were excluded from the analysis (p 0.001). However, no statistical difference was found in infection rates. A battery pocket hematoma was observed in 4 patients, and 1 patient with a possible battery pocket infection. Conclusion: We think that the low rate of CIED infection in our clinic is a result of strict periprocedural measures and collaboration with infectious diseases.